2022
DOI: 10.1136/bjsports-2021-104978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with osteoarthritis and pain in retired Olympians compared with the general population: part 2 – the spine and upper limb

Abstract: Objectives(1) To determine the prevalence of spine and upper limb osteoarthritis (OA) and pain in retired Olympians; (2) identify risk factors associated with their occurrence and (3) compare with a sample of the general population.Methods3357 retired Olympians (44.7 years) and 1735 general population controls (40.5 years) completed a cross-sectional survey. The survey captured demographics, general health, self-reported physician-diagnosed OA, current joint/region pain and significant injury (lasting ≥1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Collectively, these studies suggest former athletes may be fitter, healthier and stronger well into midlife and older age,73 despite high rates of radiographic OA 72. It is possible that former athletes benefit from persistently greater quadriceps muscle strength, which could help preserve better function,74 and/or high cardiorespiratory fitness, which could (partially) counteract deleterious consequences of higher OA prevalence 6 7 72 75. Future studies could investigate the effect of prior sports participation on cardiorespiratory fitness and function in midlife and older adults who have OA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Collectively, these studies suggest former athletes may be fitter, healthier and stronger well into midlife and older age,73 despite high rates of radiographic OA 72. It is possible that former athletes benefit from persistently greater quadriceps muscle strength, which could help preserve better function,74 and/or high cardiorespiratory fitness, which could (partially) counteract deleterious consequences of higher OA prevalence 6 7 72 75. Future studies could investigate the effect of prior sports participation on cardiorespiratory fitness and function in midlife and older adults who have OA.…”
Section: Discussionmentioning
confidence: 97%
“…Participating frequently in competitive sports may have beneficial and harmful long-term health implications, as athletes often engage in vigorous intensity exercise and strength-training yet are also exposed to high training loads and musculoskeletal injury risk. Recently published studies suggest former athletes live longer than age-matched peers3–5 yet also have a higher risk for lower extremity osteoarthritis (OA) and joint replacement 6–8. A systematic review and meta-analysis of cardiovascular disease risk factors in male former team-sport athletes found inconsistencies in the reporting of cardiovascular disease risk factors and inconclusive results 9.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although low back pain is common in the general population (11.9% 6 2%), 19 a study of 3357 retired Olympians showed that the odds of lumbar spine pain (19.3%) was greater in the athlete population than in the general population. 20 Golfers reporting an injury complaint were significantly older, rated their daily train environment poorly with less accessibility to health support staff, and were more likely to train/compete with injury and pain. Studies of elite beach volleyball players 21 and aquatic athletes [22][23][24][25] similarly show that athletes train and compete with injury, emphasizing the importance of access to health care during training, and the need to implement injury prevention exercises.…”
Section: Injury-complaintsmentioning
confidence: 98%
“…However, these studies are limited to data capture during a 3-week window, once every 4 years for summer and winter sports athletes 1. While retired athlete studies offer insights covering longer periods of time, these are often cross-sectional, and there are limitations in terms of recall bias due to the retrospective nature of injury history questions 3–5. Some national sport bodies monitor injury longitudinally but these season-based studies are few and far between 7 8…”
Section: Limitations To Current Knowledgementioning
confidence: 99%
“…In a recent retired Olympian study, 63% of Olympians reported having had at least one significant injury at some point during their career 2. Significant joint injury is a known risk factor for the development of osteoarthritis (OA), and in retired athletes there is evidence of an association between joint injury and ongoing pain, and the development and progression of OA 3–5. The rates of pain and post-traumatic OA are also reported to be higher for retired athletes when compared with the general population.…”
mentioning
confidence: 99%